SYNTHESIS AND CHARACTERIZATION OF PHOTOCATALYS Fe2O3 PILLARED MONTMORILLONITE DOPED TiO2 AND ITS APPLICATION FOR RHODAMINE B PHODODEGRADATION USING VISIBLE LIGHT IRRADIATION - Dewi, D. A. D. N.; Simpen, I N.; Suarsa, I W. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020DO - 10.24843/JCHEM.2020.v14.i01.p14, 2020)
A montmorillonite clay modified with semiconductor metal can act as a photocatalyst material. Montmorillonite clays were chosen because of their natural characteristics which are easily to be modified and have high specific surface area. This research aims to modify montmorillonite clay into photocatalyst material. The montmorillonite clay was intercalated using Fe 2 O 3 to produce Fe 2 O 3 -pillared montmorillonite clay, then doped with TiO 2 to form a photocatalyst material Fe 2 O 3 -PILC / TiO 2 . Modifications were intended to increase the specific surface area and number of active photocatalyst sites and thus increase the ability of photodegradation. The characterization carried out included characterizing the pillar formation using X-ray Diffraction (XRD), specific surface area by the BET method (Bruneau, Emmet, and Teller), a the number of surface acid-base sites by the titration method. Photocatalyst with the best character was Fe 2 O 3 -PILC / TiO 2 1: 3 with specific surface area, number of acid and base sites respectively 45,947 m 2 /g, 20,1736 x 1023 sites/gram and 19,0044 x 1023 sites/gram. The result of photodegradation at optimum condition with visible light at pH 3 using 400 mg photocatalyst was 99.84%.   Keywords: photocatalyst, Fe 2 O 3 , montmorillonite clay, TiO 2 , rhodamine B